Misconceptions about Chronic Obstructive Lung Disease - A Questionnaire Study - Konuk, Suat (Archives of Clinical and Biomedical Research, 2017)
Background: The aim of our study was to ask the patients the questions if COLD was contagious and if COLD was an abbreviation and if so, what were the meanings of the relevant initials and evaluate the answers. Materials and Methods: Men and women aged above 35 years who were diagnosed with COLD in Düzce It was planned to ask the participants the following questions separately: “Is this disease contagious?”, “Is COLD an abbreviation, and if so, what is the meaning of the initials?” and to evaluate the answers. Results: A total of 504 individuals (112 women and 392 men) who completed the questionnaire successfully were included in the study. 31.6% of the individuals who participated in the study knew that COLD was not contagious. When the questions if COLD was an abbreviation, and if so what were the meanings of the initials were asked separately, 21% of the participants stated that the word COLD was an abbreviation and 21.7% knew the meanings of the initials. Conclusion: The study demonstrates that physicians who treat COLD should give their patients more and explanatory information. In addition, we should clearly explain to each of our patients who have been diagnosed with COLD and are being treated with drugs for COLD that the disease is a chronic lung disease and leads to obstructive dyspnea(causing difficulty in breathing). Another notable point is that knowing that COLD is not contagious is important in terms of prevention of both ostracisation and isolation of the patient.